2003
DOI: 10.1097/01.alc.0000102720.08798.51
|View full text |Cite
|
Sign up to set email alerts
|

Pain Thresholds in Alcohol Preferring and Non‐preferring Rats: Diurnal and Repeated Trial Line Differences

Abstract: The alcohol preferring HAD1 line demonstrates a significantly increased baseline tail latency compared to the nonpreferring LAD1 line in both light and dark phases. There is a significant diurnal rhythm of paw and tail latency in both of the alcohol preferring lines (iP5C and HAD1) but not in the nonpreferring lines (iNP1 and LAD1). A novel finding of Decline in Latency with Repeated Trials (DLRT) was found in both alcohol preferring and nonpreferring lines; degree of DLRT differed as a function of line and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Alcohol abuse may either lead to increased pain sensitivity or share a common underlying cause such as a genetic vulnerability. For example, alcohol‐preferring rats have decreased tolerance of pain as compared with non‐alcohol‐preferring rats [40], and both alcohol dependence and increased pain sensitivity have been linked to polymorphisms of the catechol‐O‐methyltransferase gene [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol abuse may either lead to increased pain sensitivity or share a common underlying cause such as a genetic vulnerability. For example, alcohol‐preferring rats have decreased tolerance of pain as compared with non‐alcohol‐preferring rats [40], and both alcohol dependence and increased pain sensitivity have been linked to polymorphisms of the catechol‐O‐methyltransferase gene [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, alcohol administration enhanced tolerance for a painful electric shock only in FHN subjects (Perrino et al, 2008) whereas a more comprehensive study (Ralevski et al, 2010) found that FHP subjects scoring high for neuroticism displayed greater alcohol analgesia than FHN subjects and FHP subjects with low neuroticism scores. Studies in rodents selectively bred for differences in alcohol preference also provide partial evidence alcohol preference and pain response covary (Chester et al, 2002; Kampov-Polevoy et al, 1996; but see Kimpel et al, 2003). Given the possibility of a genetic link between pain processing and alcohol dependence, we suggest possible candidates having the potential to influence neurotransmitter systems involved in alcohol dependence and pain.…”
Section: Genetic Influences On Pain Alcohol Analgesia and Alcoholmentioning
confidence: 99%
“…There are a number of neurochemical characteristics within these systems that are associated with, and may be causally related to, differences in alcohol intake (Badia-Elder et al, 1999;Froehlich et al, 1998;Froehlich and Li, 1989, 1994Wand, 1996, 1997;Gong et al, 1997;Kimpel et al, 2003Kimpel et al, , 2007.…”
Section: Utility Of Rat Lines Selectively Bred For Differences In Alcmentioning
confidence: 99%